PROBIOTIC EFFECT OF Lactobacillus isolates AGAINST BACTERIAL PATHOGENS IN FRESH WATER FISH - D Dhanasekaran; Subhasish Saha; N Thajuddin; M Rajalakshmi; A Panneerselvam (JOURNAL OF COASTAL DEVELOPMENT, 2010)
A total of 59 Lactobacillus isolates were isolated from 5 different fresh water fish such as Cat fish ( Clarias orientalis)  , Hari   fish (Anguilla sp), Rohu fish ( Labeo rohita),  Jillabe  fish (Oreochromis sp) and Gende  fish    ( Punitus carnaticus). Among the 59 isolates only 4 Lactobacillus isolates were selected for further study. Based on morphological and biochemical characteristics, the isolates were identified as Lactobacillus sp. The pathogen were isolated from infected cat fishes, characterized and identified as Vibrio parahaemolyticus, Aeromonas sp and Aeromonas salmonicida. The Lactobacillus isolates were screened for antagonistic activity against Aeromonas, Vibrio sp. by agar diffusion assay. Among the 4 isolates, Lactobacilli RLD2 showed significant antagonistic activity against Aeromonas and Vibrio sp alone. and was further evaluated by standard plate count assay for the viability of pathogen. The isolate was multiplied and the fish feed was supplement with Lactobacillus isolates. The results reveal that the size, weight of the fish was statically increased in comparison to that of control fish. The present study concluded that the Lactobacillus isolates could be used as probiotic bacteria in aquaculture, to manage aeromonasis.